2015
DOI: 10.11622/smedj.2016107
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum blood loss: visual estimation versus objective quantification with a novel birthing drape

Abstract: INTRODUCTIONImmediate postpartum haemorrhage (PPH) is defined as blood loss ≥ 500 mL after normal vaginal delivery.(1-3) This obstetric complication is a leading cause of maternal death worldwide. To prevent the occurrence of PPH, current evidence supports active management of the third stage of labour, especially the prescription of oxytocin, as standard obstetric care.(1-3) However, the optimal method for determining the volume of postpartum blood loss for early detection of PPH remains unclear.Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 17 publications
(39 reference statements)
3
47
0
Order By: Relevance
“…One proposal was dismissed in the first round feedback that standardized visual estimation training should be canceled for its inaccuracy. 21 While it is true that objective measurements are favored, 22 we should not deny that visual estimation is widely used as a rapid way to suspect PPH and activate the patient assessment, 23 especially when obstetrical workload is so prominent for such an enormous population. That is why we are currently processing a systematic training protocol, and designing the evaluation method.…”
Section: Discussionmentioning
confidence: 99%
“…One proposal was dismissed in the first round feedback that standardized visual estimation training should be canceled for its inaccuracy. 21 While it is true that objective measurements are favored, 22 we should not deny that visual estimation is widely used as a rapid way to suspect PPH and activate the patient assessment, 23 especially when obstetrical workload is so prominent for such an enormous population. That is why we are currently processing a systematic training protocol, and designing the evaluation method.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size for this study was calculated using the incidence of PPH from our previous study, which found an increase in postpartum hemorrhage from 3.5% to 9.1% when comparing the subjective visual estimation method with the objective sterile under-buttock drape method, respectively. 9 We used a type 1 error of 0.05 and a type 2 error of 0.2, and the ratio between the groups was 1:1. The calculation plus a 10% increase to compensate for errors of any type yielded a minimum sample size of at least 396 patients per group.…”
Section: Sample Size Calculation and Statistical Analysismentioning
confidence: 99%
“…6,8 A study conducted by our team in 2013, which evaluated postpartum blood loss measured in 100 mL discreet categories, confirmed the inaccuracy and underestimation of the visual estimation method when compared with objective measurement using a sterile under-buttock drape (low correspondence and poor agreement, with a Cohen's kappa coefficient of 0.07; p < 0.05). 9 In 2014, our center implemented a new protocol to evaluate postpartum hemorrhage by an objective measurement of postpartum blood loss using a postpartum drape with a calibrated bag (PDCB). In this protocol, postpartum blood loss ≥ 350 mL is considered to be an early warning sign for PPH.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique is complicated, costly and impractical. It cannot be applied at all levels of healthcare and is more suitable for clinical research (23)(24)(25). Weighed soaked swabs or drapes after delivery are also used for early detection of PPH (26).…”
Section: Introductionmentioning
confidence: 99%